Live Sound Mixing For Beginners: An Illustrated Guide To Essential Equipment & Concepts - Ng, Lester (Independently published, 2021)
Want to learn about live sound in an easy-to-understand manner? Live Sound Mixing For Beginners covers all the essential information you need to learn about operating a sound system for a live event. Find out what to listen for, how to connect up your equipment and how to make use of it all with simple, straightforward explanations. LIve Sound Mixing For Beginners is ideal for the person who needs to quickly get up-to-speed on how to make use of sound systems. Whether it be for a corporate setting, in a school or a house of worship, the book covers how to get the most out of your equipment. You will learn about how a sound system is setup and how to make use of a mixer. Also learn about how to listen out to what is coming through the sound system in order to determine if it is performing well. Find out: how to set up a sound system what to listen out for in a sound system how to use a mixer what sound processing effects such as equalizers, compressors and reverb units do, and how to apply them different situations basic mixing principles how to run a sound check Live Sound Mixing For Beginners is the ideal book for anyone who is getting into live sound systems, or who wishes for a book which consolidates all the essential information in one book.